Facile preparation of polyimide/graphene nanocomposites via an in situ polymerization approach. Issue 5 (13th January 2017) - Qin, Songlv; Chen, Cheng; Cui, Mingjun; Zhang, Afang; Zhao, Haichao; Wang, Liping
Abstract : In this study, to achieve a compatible and good dispersion of graphene in polyimide matrix, we synthesized an aromatic diamine, aniline trimer, as a polymerizable graphene dispersant. Abstract : In this study, to achieve a compatible and good dispersion of graphene in polyimide matrix, we synthesized an aromatic diamine, aniline trimer, as a polymerizable graphene dispersant. Polyimide/graphene nanocomposites with 0.25–2% mass fraction of graphene were prepared by in situ condensation of pyromellitic dianhydride, 4, 4′-oxydianiline, and aniline trimer (AT) functionalized graphene in DMAc, following subsequent thermal imidization at elevated temperatures. UV-vis and Raman spectroscopy verified the π–π interactions between AT and graphene. The microstructure analysis using XRD, SEM, and TEM were performed to investigate the morphology of graphene in the polyimide matrix. The thermal, mechanical, and tribological properties of polyimide/graphene nanocomposites were investigated by TGA, DMA, and friction and wear tests. In view of the ease of preparation and their superior physical properties over neat polyimide, PI/G composites prepared in this study showed promising applications as wear-resistant and self-lubricating materials.